O portal do professor do MEC: uma análise das sugestões de aula através dos pressupostos de Paulo Freire - Pereira, Mikaelly Cristiny de Almeida (2021)
The aim of this research is to analyze the Suggestions of Lessons from the MEC Teacher Portal according to Paulo Freire's Theoretical Assumptions for Youth and Adult Education, as he is a reference in the trajectory of this modality in Brazil and established principles that when used correctly, they are able to supply the specific needs and singularities of this modality. Thus, concepts identified in Freire's works were selected for analysis, namely education as a political act, a dialogic act and as an act of knowledge. As the Portal is a platform created by the Ministry of Education in 2007 with the aim of assisting in the teaching and learning process of regular education, there is a need to investigate how the Ministry of Education has attended to EJA in this Portal. Through documentary research and the use of content analysis techniques, some approximations and distances were identified in the Suggestions of Lessons in relation to Freire's Assumptions. Based on the results obtained in the analyzes and the study of Freire's works, it is concluded that, in order to fulfill what Paulo Freire proposes for EJA, the three assumptions must be used during the construction of knowledge in the classroom, however, in the Most of the Suggestions for Lessons analyzed are not identified simultaneously, thus indicating a limitation of the Suggestions for Lessons in attending important aspects of EJA pointed out by Freire.